1D model for n-butane adsorption and thermal variation for EVAP canister of gasoline-fueled vehicles: Validation with experimental results and DFSS optimization. (5th June 2022) - Romagnuolo, Luca; Frosina, Emma; Fortunato, Francesco; Andreozzi, Assunta; Senatore, Adolfo
Abstract: Gasoline evaporation from vehicle fuel tanks is a major source of VOCs, that represents a serious threat for both human health and environment. To limit these emissions, the most adopted strategy is to use a carbon canister filter to store fuel vapors and then burn them inside the engine along with the fresh charge. However, the canister saturation level is usually unknown, and it can easily reach the full saturation, especially in particular conditions. As hybrid vehicles are becoming more popular in the market, this issue becomes even more important, since canister purging phase has even less time to be performed. In this activity, a 1D transient, non-isothermal, non-adiabatic model has been developed to specifically simulate the carbon canister filter of a common EVAP system and analyze its behavior during fuel vapor adsorption, with particular attention to the mutual influence of carbons adsorption performance and temperature variation. The model presented is based on an adsorption isotherm derived from the potential theory of adsorption, and it has been developed to be usable with only few canister properties. A system of two coupled PDEs has been coded and solved in MATLAB® environment, and results have been compared to experimental data in terms of mass and internal temperature variation on a common European canister, found in a previous study, with a standard loading flow rate of n-butane mixture and standard environmental temperature. The model has then been analyzed by using the Design For Six Sigma (DFSS) method, which has allowed a good optimization on calibration parameters with a relatively low amount of tests. Results show a significant increment in the predictive capabilities of the optimized model (up to 90% of the experimental value), with respect to the first simulations. This model helps to understand and evaluate the influence of environmental temperature on the canister filter performance, and can be used for both canister design and control of the purging strategies performed by an on-road vehicle. Highlights: A carbon canister filter can easily reach saturation in gasoline/hybrid vehicles. Activated carbons adsorption performance is strongly dependent on temperature. A 1D model has been developed to analyze and predict adsorption inside canister. Thermal data used to calibrate the geometrical parameters of the model. A DFSS analysis has been performed to optimize calibration parameters of the model.